Effect of motives on sustainability performance of tourist hotels: Mediating role of sustainability adoption - Wijesundara, Namal; Khatibi, Ali; Azam, S. M. Ferdous; Tham, Jacquline (Goodwood Publishing, 2025)
Purpose: This study examines how sustainability adoption mediates the relationship between sustainability motives and performance of tourist hotels in Sri Lanka. Research Methodology: To check the proposed hypotheses of this quantitative investigation, a Structural Equation Model was utilized as an analytical technique using 207 datasets from registered tourist hotels in Sri Lanka. The questionnaire survey technique was used to collect the data. Results: The structural model analysis revealed that while managerial motivations significantly enhance sustainability performance when mediated by corporate sustainability adoption, stakeholder and institutional motivations do not exhibit the same mediating effect. Limitations: This study is confined to the Sri Lankan hotel industry, which may limit the generalizability of the findings to other countries. Focusing solely on tourist hotels may limit the applicability of these results to other industries. The use of cross-sectional data limits one’s ability to infer causal relationships over time. Contribution: The contributions of both theory and practice are profound, advocating a strategic focus on internal leadership to drive sustainability in the lodging industry. Future research should explore these relationships across different sectors to enhance our understanding of the factors that foster sustainability initiatives. Implications: The findings emphasize the significance of internal leadership and managerial motivations, rather than external motives, in driving sustainability efforts toward the sustainability performance of hotels. This justifies the need for change in the literature on sustainability, with a greater focus on the role of managerial commitment as a critical component in attaining sustainable performance. Novelty: These findings challenge the conventional wisdom that external pressures alone can drive sustainability success, and highlight the importance of internal leadership and managerial commitment.